Investigation on Solid State Nd-YAG nanosecond Laser Assisted Shock Peening of Miniature Gears. (2015) - Raj, Deepak; Tyagi, Ruchir; Chaubey, Sujeet Kumar; D'Souza, Agnel; Palani, I.A.; Jain, N.K.
Abstract: The aim of this paper is to investigate effects of Nd-YAG Laser Shock Peening (LSP) process on the mechanical properties of the teeth surface of Stainless Steel (SS-304) miniature gears. Laser power has been varied from 30 mW to 250 mW and finally performed on 75 mW after optimization. The laser interaction time was kept 60 seconds Micro-hardness of the LSP-treated sample was measured using a Vickers diamond indenter depending on the depth. Hardness value has been found to increase from 241HV to 277HV. Modification in the microstructure has been analyzed using Scanning Electron Microscope(SEM) images. Characterization has been done using X-ray diffraction (XRD) and SEM techniques on the gear sample to compare modification in properties. Firstly all laser parameters have been optimized to prevent crack initiation and propagation. Depth of peening was analysed after laser treatment over two different laser wavelengths to ensure proper peening. It was found to be around 0.3 mm. Roughness of the gear teeth surface was measured before and after peening. Finally a comparative study has been done on the mechanical properties at two different wavelengths of 532 nm and 355 nm. Optimization of time duration of peening has also been done.